Kajian Potensi Kawasan Situs Batu Penggilingan Cakung Jakarta Timur sebagai Kampung Wisata Warisan Budaya Betawi - Sri Prasetya Widodo; Uras Siahaan; Margareta Maria Sudarwani (Fakultas Teknik - Universitas Bung Karno, 2023)
The preservation of the city's historical artifacts is part of the development of the historical, memory and cultural sustainability of the city. The edge of the Buaran River has the potential for historical objects in the form of Batu Penggilingan sites, the history of the area and the potential for residents to develop their villages. This article raises a study of cultural values, preservation and development of Batu Penggilingan historical site on the banks of the Buaran River, Cakung, East Jakarta. This study examines its development as a Betawi cultural tourism village so that it can make the area an educational and interesting tourist attraction. This study used descriptive qualitative methods based on field empirical data exploring the factors that support the program. The result of the discussion was that the development of tourism villages requires in-depth identification of physical, architectural and environmental potentials in order to become a sustainable program by paying attention to and strengthening the unique Betawi cultural characteristics in the village planning and design process.